Product Market Competition Dalam Menilai Corporate Risk Taking Dan Efisiensi Investasi - Yuni Maryana; Andi Irfan*; Tasriani Tasriani (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
Corporate decisions are the parent of a company's survival. Corporate decisions are divided into two, namely corporate risk taking and efficiency investment. This study aims to analyze the effect of product market competition on corporate decisions, especially on corporate risk taking and investment efficiency. The main measure of product market competition is based on the level of the Herfindahl Hirschman Index (HHI). In this study the authors used MANOVA analysis to examine the relationship between product market competition (as an independent variable) on corporate risk taking and overinvestment (as the dependent variable) in multivariate and univariate ways. By using observations of manufacturing companies listed on the IDX in 2015-2020, a sample of 71 companies was obtained using a purposive sampling method. Based on the results of the multivariate test analysis that has been carried out in this study, it was found that product market competition has a significant effect on corporate risk taking and overinvestment, while based on the univariate significant test (test of between subjects-effect) product market competition has a significant effect on corporate risk taking while product market competition on overinvestment does not show a significant effect. So it can be concluded that competition acts as a mechanism for disciplining corporate decisions.